Pengaruh Story Telling terhadap Penurunan Tingkat Nyeri pada Ibu Hamil Trimester III - Mufidah Mufidah; Rani Safitri (Lembaga Pengembangan Kinerja Dosen, 2026)
Pain in third-trimester pregnant women is a common complaint due to physiological changes, weight gain, uterine enlargement, and pressure on the musculoskeletal structure. This condition can cause discomfort, disrupt daily activities, and even affect the quality of life of pregnant women. One non-pharmacological intervention that can be used to help reduce pain levels is storytelling. This method provides cognitive distraction so that the mother's attention is diverted from the sensation of pain. This study aims to determine the effect of storytelling on reducing pain levels in third-trimester pregnant women. This study used a quantitative design with a comparative approach between the control group and the intervention group. The study sample consisted of 30 third-trimester pregnant women divided into two groups, each with 15 respondents. The sampling technique used total sampling. Data were analyzed using cross-tabulation to determine differences in pain levels between the two groups. The results showed that all respondents in the intervention group (100%) experienced mild pain after being given storytelling. Meanwhile, in the control group, the majority of respondents experienced severe pain (11 people (73.3%) and moderate pain (4 people (26.7%). Storytelling has an effect on reducing pain levels in third-trimester pregnant women. This intervention can be used as a non-pharmacological alternative that is safe, simple, and easy to implement in midwifery practice.